Is maple syrup the next sweetener substitute? Comparing the potential opportunities and challenges of maple syrup to other common sweeteners - Ihsan Shawki Akili; Corina Miko; Patrick J. Shafer; Rebecca L. Hagedorn-Hatfield; Derek C. Warren; Jana Kraft; Janet C. Tou; Mark L. Isselhardt; R. Chris Skinner (Journal of Agriculture and Food Research, 2025)
Maple syrup has been a long-time favorite breakfast topping; however it has recently been receiving heightened attention as a potential healthier sweetener alternative. Although maple syrup is a high-sugar sweetener, it also contains properties, such as antioxidant polyphenols, associated with positive health outcomes. To date, very little research has been done to critically evaluate maple syrup's impacts on health and maple syrup remains understudied compared to the most common sweeteners. In addition to nutrient content and health, maple syrup differs in production and food science applications compared to other common sweeteners. Unique challenges also face maple syrup, including higher production and sale costs, potential climate change impacts on syrup production, and more. To better understand and evaluate maple syrup's potential as a sweetener replacement, further investigation considering all of these aspects is needed. Using common research engines (Google Scholar, PubMed, etc.) we searched for published articles on the various sweeteners and key focus areas detailed in this review. Here, we provide a broad overview of maple syrup compared to other common sweeteners, with an emphasis on untangling the excitement around maple syrup and health and the research that has been conducted on the sweet topping.